Rebranding equality: Malaysia’s progress on women’s rights advocacy - Nik Salida Suhaila Nik Saleh,; Wan Abdul Fattah Wan Ismail,; Syahirah Abdul Shukur, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Even though equality has been described as a simple concept, its meanings and principles have not been properly understood by the public. Similar treatment might not have a value of neutrality because, once the right to equality is related to and enforced by laws, its objectivity and impartiality can be challenged. The Malaysian government is making progress towards a safer and more equal environment for women and girls following the proposed new or amended legislation. These includes the anti-stalking law, the Sexual Harassment Act, and ending child marriage. Furthermore, the establishment of a Select Committee on Rights and Gender Equality in Parliament have been considered as a good step forward for equality. Indeed, implementation of policies such as childcare facilities in government offices as well as encouraging the private sector to follow suit are good moves towards creating more opportunities and encouraging the participation of women in the workforce. This paper explores the conceptual understanding of ‘equality’ globally and from the perspective of Islamic jurisprudence. This reflection is in line with Islamic belief that needs to reform the understanding of society based on the suggestion of Al-Quran and Islamic scholars. With this interpretation, this paper will explore Malaysia’s progress in empowering women and gender equality. Finally, this paper will suggest a way forward for Malaysia to empower women that have been marginalized and subordinated.